Conceptual Approaches to Understanding the Essence of Proof in the Science of Criminal Process in Ukraine - VAPNIARCHUK, Viacheslav V.; KAPLINA, Oksana V.; SHUMYLO, Mykola Ye.; TUMANYANC, Anush R. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The relevance of the issue stated in the paper is conditioned upon the existence of different scientific views in the science of the criminal process, both as to the essence of proof at large, and in relation to its individual institutions, categories and concepts, which were determined both by a philosophical and methodological basis inherent in certain periods of history, and by features of statutory regulation. The purpose of the paper is to distinguish scientific approaches (interpretations, concepts) to criminal procedural proof and substantiation of the expediency of isolation and use of the author's (complex and systemic) approach. The main approach to the study of this problem was to systematize approaches to criminal procedural proof on the basis of its substantive and functional understanding and to express critical (in both positive and negative terms) opinions on each of them. The paper proposes the identification of four different approaches to understanding the essence of criminal procedural proof: cognitive (wherein two types of interpretation are distinguished: logical (rational) and rational-empirical); active; integrated; complex and systemic. The materials of the paper represent both theoretical and practical value. They can be used for further scientific investigation of the nature of proof in criminal proceedings, as well as for the proper understanding and implementation of law enforcement criminal proceedings.